The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s00431-019-03543-0
|View full text |Cite
|
Sign up to set email alerts
|

End-tidal carbon dioxide levels during resuscitation and carbon dioxide levels in the immediate neonatal period and intraventricular haemorrhage

Abstract: Abnormal levels of end-tidal carbon dioxide (EtCO 2 ) during resuscitation in the delivery suite are associated with intraventricular haemorrhage (IVH) development. Our aim was to determine whether carbon dioxide (CO 2 ) levels in the first 3 days after birth reflected abnormal EtCO 2 levels in the delivery suite, and hence, a prolonged rather than an early insult resulted in IVH. In addition, we determined if greater EtCO 2 level fluctuations during resuscitation occurred in infants who developed IVH. EtCO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
(23 reference statements)
0
12
0
Order By: Relevance
“…We have reported that abnormal levels of carbon dioxide, including large magnitude of difference in CO 2 levels during resuscitation contribute to IVH development [ 20 ]. A previous retrospective study reported the maximum PCO 2 during the first 72 hours after birth was a dose-dependent predictor of severe IVH development [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have reported that abnormal levels of carbon dioxide, including large magnitude of difference in CO 2 levels during resuscitation contribute to IVH development [ 20 ]. A previous retrospective study reported the maximum PCO 2 during the first 72 hours after birth was a dose-dependent predictor of severe IVH development [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the first few days after birth, the respiratory and circulatory conditions of neonates undergo considerable changes. Some studies have shown that inappropriate EtCO 2 within a few days after birth in preterm infants is associated with PVL [ 2 , 3 ], IVH [ 1 , 11 , 12 ], and BPD [ 4 ]. Therefore, it is important to monitor CO 2 and control the PaCO 2 appropriately in preterm infants immediately after birth to reduce the risks of these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring the pattern of cerebral oxygenation using NIRSdetermined rScO 2 as early after birth as possible, preferably already on the resuscitation table, at least up to postnatal day 4 in these vulnerable group of neonates can alert the clinician at an early point in time for hypercapnia-induced hyperoxygenation/hyperperfusion [25,35] and hypoxia-or hypocapnia-induced underoxygenation/hypoperfusion [32] of the immature brain. A very recent study from Tamura et al [37] showed that hypercapnia in the delivery room was associated with the occurrence of all grades of PIVH in a large cohort of preterm infants. Alderliesten et al [35] showed supranormal rScO 2 values [17] during 24 h preceding PIVH in a case-control study of 650 preterm infants below 32 gestational weeks.…”
Section: Mechanisms Of Brain Injury In the Preterm Infant And Cerebral Oxygenationmentioning
confidence: 99%
“…It may be clear that prevention or early recognition and down tuning of cerebral hyper(hypo-)perfusion/-oxygenation and/or a fluctuating pattern of the cerebral blood flow potentially reduce or even prevent the occurrence and extension of PIVHs. In this respect it is especially important to aim for a stable arterial carbon dioxide level within normal limits (i.e., [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. Monitoring the pattern of cerebral oxygenation using NIRSdetermined rScO 2 as early after birth as possible, preferably already on the resuscitation table, at least up to postnatal day 4 in these vulnerable group of neonates can alert the clinician at an early point in time for hypercapnia-induced hyperoxygenation/hyperperfusion [25,35] and hypoxia-or hypocapnia-induced underoxygenation/hypoperfusion [32] of the immature brain.…”
Section: Mechanisms Of Brain Injury In the Preterm Infant And Cerebral Oxygenationmentioning
confidence: 99%